Are Losses from Natural Disasters More Than Just Asset Losses? : The Role of Capital Aggregation, Sector Interactions, and Investment Behaviors - Hallegatte, Stephane; Vogt-Schilb, Adrien (World Bank, Washington, DC, 2016)
The welfare impact of a natural disaster depends on its effect on consumption, not only on the direct asset losses and human losses that are usually estimated and reported after disasters. This paper proposes a framework to assess disaster-related consumption losses, starting from an estimate of the asset losses, and leading to the following findings. First, output losses after a disaster destroys part of the capital stock are better estimated by using the average—not the marginal—productivity of capital. A model that describes capital in the economy as a single homogeneous stock would systematically underestimate disaster output losses, compared with a model that tracks capital in different sectors with limited reallocation options. Second, the net present value of disaster-caused consumption losses decreases when reconstruction is accelerated. With standard parameters, discounted consumption losses are only 10 percent larger than asset losses if reconstruction is completed in one year, compared with 80 percent if reconstruction takes 10 years. Third, for disasters of similar magnitude, consumption losses are expected to be lower where the productivity of capital is higher, such as in capital-scarce developing countries. This mechanism may partly compensate for the many other factors that make poor countries and poor people more vulnerable to disasters.